Pengaruh Kepemimpinan Terhadap Keterlibatan Pegawai Dan Kinerja (Studi pada Sektor Publik) - Khuzaini . Khuzaini; Basuki - Basuki; Rahmi Widyanti; Deli Anhar (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
Leadership in an organization is a central position in moving employees to achieve optimal performance. This research aims to analyze the influence of leadership on employee performance in the public service sector with employee involvement as a mediating variable. Data analysis uses path analysis. This research also describes the variables of leadership, involvement and employee performance using a questionnaire. This research tries to prove that employee involvement is a variable that influences employee performance so that employee involvement acts as a mediating variable.